The Effect of Real-Time Biofeedback on Lumbar Spine and Lower Limb Kinematics and Kinetics During Repetitive Lifting - Naudé, Yanto (Auckland University of Technology, 2018)
The incidence of low back pain (LBP) in occupations that involve repetitive lifting is disproportionately high compared to other physical occupations. This has been attributed to prolonged and sustained end range spinal flexion over a working day, often due to impairments in postural awareness related to fatigue and creep. Physiotherapists will often provide advice on manual handling techniques to improve lifting posture, however, adherence is often brief and not easily transferable to the workplace. This has prompted health practitioners to find alternative workplace interventions approaches, such as real-time biofeedback. A systematic review was initially conducted of randomised and non-randomised studies to determine the level of clinical evidence for real-time postural biofeedback as an approach to changing spinal posture. The review identified a low level of clinical evidence for the use of biofeedback as a treatment adjunct to effect changes in spinal posture, primarily due to the small number (8) of low quality studies. No studies considered the influence of biofeedback during highly repetitive manual handing tasks, where the ability to affect postural changes may be compromised due to fatigue. An experimental study was conducted with the primary aim of assessing the effectiveness of real-time postural biofeedback on modifying lumbosacral (LS) posture during a repetitive lifting task. A secondary aim was to investigate the biomechanical changes (kinetic and kinematic) on the lumbar spine and lower limbs. Thirty-four participants were randomly allocated to 2 groups: a biofeedback (BF) / intervention group; and a non-biofeedback (NBF) / control group. Participants lifted a 13kg box at a frequency of 10 lifts per minute for up to 20 minutes. Two wireless inertial sensors attached to the lumbar spine provided real-time biofeedback on lumbar posture when lumbar flexion exceeded 80% maximum flexion. A nine-camera motion analysis system was used to record three dimensional (3D) motion, and in conjunction with 3D ground reaction forces, provided kinematic and kinetic data for input into a biomechanical model used to estimate joint reaction forces and joint moments. Bending moments on the passive structures of the lumbar spine were also calculated. Ratings of perceived exertion (RPE) were recorded throughout the lifting task. Biofeedback resulted in significantly reduced peak lumbar flexion over the duration of the task, compared to the NBF condition. The BF group was able to maintain a LS sagittal plane posture within the designated range (<80% maximum flexion), whereas, the group without feedback displayed a linear increase in trunk and LS flexion, reaching approximately 99% of maximal flexion at 20-minutes. Furthermore, the BF group adopted greater knee flexion, and increased hip and knee extension angular velocities compared to the NBF group. Whilst there were no differences between groups in the bending moment on the lumbar spine, estimates of biomechanical loads on the passive structures of the lumbar spine showed significant differences. Participants who received biofeedback did not become reliant on feedback, as demonstrated by reaching a peak after seven minutes of lifting followed by a progressive decline in the amount of feedback. Although the BF group might be considered to have adopted a physiologically more challenging lifting posture (i.e. semi-squat type posture), ratings of perceived exertion (RPE) suggested no difference between groups. Providing biofeedback on lumbosacral flexion (LSF) during repetitive lifting appears beneficial in avoiding end range of LF and reducing the passive loading on the musculoskeletal structures of the lumbar spine. Thus, biofeedback of the LS posture offers a potential preventative and treatment adjunct to educate clients about their lifting posture. This could be particularly important for young, inexperienced workers employed in repetitive manual handling who appear at increased risk of back injury. When presented with biofeedback on lumbar posture, a strategy adopted by participants involved increased knee and hip angular velocities. Therefore, it may be prudent to consider lower limb power training, such as plyometrics, as part of an educational lifting programme.
Keywords: Biofeedback; Lumbar spine; Lower back; Repetitive lifting